An African affair - Darnton, Nina. (New York : Viking, 2011)
After the assassination of a prominent Nigerian politician, New York journalist Lindsay Cameron moves to Lagos to follow a trail of corruption, drug smuggling, and murder. What begins with the most coveted of interviews- a rare exclusive with President Michael Olumide- quickly spirals into sinister territory when a young opposition leader goes missing, his disappearance suspiciously ignored by the authorities, Nigerian and American alike, even as Olumide's promise to hold free elections is cast in doubt. As Lindsay races her colleagues to penetrate the intricate network of government thugs, Western diplomats, and CIA agents who run the Nigerian show, her entanglements with a rare-art dealer lead her still deeper into terrain that's confounding in every respect- from matters of the heart to those of politics and trade that have enshrouded an entire nation in greed and malfeasance of deadly proportions.--From book jacket.
Keywords: Women journalists -- Fiction; Americans -- Nigeria -- Fiction; Assassination -- Nigeria -- Fiction; Organized crime -- Nigeria -- Fiction; Lagos (Nigeria) -- Fiction; Romantic suspense fiction